Japan’s Aging Society: A Challenge to Japan’s Diversity & Social Inclusion - Fransisca Fleicia Paschaline; Rama Ardhia Prastita; Ericka Mega (Department of International Relations, Brawijaya University, 2023)
Japan is a super-aged society. The combination of high life expectancy and low fertility rates leads to a decreasing population. The situation is so chronic that at the extreme consequences, Prime Minister Fumio Kishida warned Japan was